MALDI MS-Based Investigations for SARS-CoV-2 Detection - Mariaimmacolata Preianò; Serena Correnti; Corrado Pelaia; Rocco Savino; Rosa Terracciano (MDPI AG, 2021)
The urgent need to fight the COVID-19 pandemic has impressively stimulated the efforts of the international scientific community, providing an extraordinary wealth of studies. After the sequence of the virus became available in early January 2020, safe and effective vaccines were developed in a time frame much shorter than everybody expected. However, additional studies are required since viral mutations have the potential of facilitating viral transmission, thus reducing the efficacy of developed vaccines. Therefore, improving the current laboratory testing methods and developing new rapid and reliable diagnostic approaches might be useful in managing contact tracing in the fight against both the original SARS-CoV-2 strain and the new, potentially fast-spreading CoV-2 variants. Mass Spectrometry (MS)-based testing methods are being explored, with the challenging promise to overcome the many limitations arising from currently used laboratory testing assays. More specifically, MALDI-MS, since its advent in the mid 1980s, has demonstrated without any doubt the great potential to overcome many unresolved analytical challenges, becoming an effective proteomic tool in several applications, including pathogen identification. With the aim of highlighting the challenges and opportunities that derive from MALDI-based approaches for the detection of SARS-CoV-2 and its variants, we extensively examined the most promising proofs of concept for MALDI studies related to the COVID-19 outbreak.